Implementation of Tree Planting and Biopore Infiltration Systems for Flood Mitigation among Junior High School Students in Pekanbaru - Yulia Setiani; Neri Puspita Sari; Silfia Rini; Sonix Gunawan (Pascasarjana Universitas Mataram, 2026)
Flooding remains one of the most common hydrometeorological disasters in Indonesia, primarily caused by reduced soil infiltration capacity, vegetation degradation, and low environmental awareness. Addressing this problem requires an integrative mitigation strategy that combines technical solutions with community-based education. This study presents a community service program aimed at improving students' environmental awareness and practical skills in flood prevention through tree planting and biopore infiltration holes at SMPN 25 Pekanbaru. The program adopted a participatory approach, including educational sessions, demonstrations, and hands-on activities. The results showed a significant increase in student knowledge, with the average score increasing from 43.6% in the pre-test to 88.4% in the post-test, representing a relative increase of 105.6%. The highest increase was observed in understanding the concept of biopores, which increased by 148.6%. Furthermore, students demonstrated increased engagement and active participation in environmental conservation practices.The uniqueness of this study lies in the integration of a simple ecotechnological solution, a biopore infiltration system, with experiential learning at the junior high school level, providing both immediate educational outcomes and long-term environmental benefits. This approach not only increases infiltration capacity and reduces surface runoff but also supports sustainable organic waste management and ecological awareness. Therefore, the proposed model can serve as an effective and applicable strategy for flood mitigation education in school-based community programs.